Physical education curriculum implementation using hyflex learning modality in the new normal - Mata, Leah; Marasigan, Arlyne (Journal of Interdisciplinary Studies in Education, 2024)
SDG 2030 Goal No. 3 highlights the importance of good health and well-being. The promotion of this goal cannot be fully realized in basic education without paying attention to physical education. The purpose of this study is to explore the implementation of the physical education curriculum using the hyflex learning modality. This study utilized a qualitative research method using a case study analysis employing focus group interviews. Purposive sampling was used to identify the participants in the study. Hyflex served as a practical modality for teachers to become efficient in responding to the context of the school. There were several opportunities observed such as accessibility and flexibility of class sessions and familiarity on the use of technology. However, challenges were also observed in technological resources, assessment and monitoring of online distance learners (ODLs), and equity and equality in learning needs. The hyflex learning modality is a practical guide for curriculum innovations in physical education and a practical modality in times of disasters or pandemic.